The great awakening : reviving faith & politics in a post-religious right America - Wallis, Jim (HarperOne, 2008)
Religious faith was a driving force behind our greatest national reforms, such as the abolition of slavery and the civil rights movement. These "great awakenings" happened periodically at crucial times in our nation's history to propel us toward the common good. The time is ripe for another movement that will transform this country. With "The Great Awakening" Wallis [rediscovers] our moral center and provides both the needed inspiration and a concrete plan to hold politics accountable and find solutions to our greatest challenges.--From publisher description.